COVID-19 booster dose acceptance, hesitancy and concerns among the elderly population: A cross-sectional study - Muhammad Imran; Zeeshan Ahmed; Azfar Athar Ishaqui; Duaa Bafail; Salman Ashfaq Ahmad; Javeria Farooq; Imran Ali; Bilal Mustafa; Tabassum Zehra; Lailoona Jaweed; Samreen Kapadia; Salman Ahmed; et al. (Journal of Infection in Developing Countries)
Introduction: The COVID-19 pandemic that originated in Wuhan, China in December 2019 results in respiratory and gastrointestinal infections. Elderly patients are at high risk. Preventive measures like avoiding contact with COVID-19 patients and wearing N95 masks can contribute to reducing the risk of infection, but vaccination remains crucial.